Time-Optimal Control Problem for a Fuzzy Object - Plotnikov, Andrej; Komleva, Tatyana; Plotnikova, Liliya; Skripnik, Natalia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
In this article one optimal control problem when the system behavior is described by linear fuzzy differential equations is considered. The conditions of its solvability are formulated, and the optimal time and optimal controls are obtained.